2017
DOI: 10.1002/ajoc.201700523
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐free, l‐Leucine‐Catalyzed Direct Dehydrative Esterification of Carboxylic Acids with Alcohols: Direct Synthesis of 3‐Alkoxy 1(3 H)‐isobenzofuranone

Abstract: Al -leucine-catalyzed mild and efficient method has been developed for the synthesis of open-chain as well as cyclic esters. Aw ider ange of alcohols, including primary, secondary,a nd tertiaryw ith aliphatic and aromatic side chains, were successfully tolerated. In the case of 2-carboxybenzaldehydes with different alcohols, 3-alkoxy-1-(3 H)-isobenzofuranones were obtained in good yields. Alcohols from natural origin have also been reacted with various acids successfully to get the corresponding esters. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…ROPTs 1 , 2 , 3 , and 4 were synthesized by the acetalization of phthalaldehydic acid (TCI; >98.0%) with methanol (Nacalai Tesque; >99.0%), 2-propanol (Nacalai Tesque; >99.0%), tert -butyl alcohol (Nacalai Tesque; >98.0%), and phenol (Nacalai Tesque; >98.0%), respectively. In­(OTf) 3 (Sigma-Aldrich or Strem; 99%) was used as a catalyst unlike the past examples (Scheme A). After the reaction for a day ( 1 ) or 3 days ( 2 , 3 , and 4 ), the reactions were quenched with Et 3 N (Nacalai Tesque; >98.0%), extracted with dichloromethane, and then washed with water ( 1 , 2 , and 3 ) or aqueous sodium hydroxide solution and then water ( 4 ), followed by brine. The organic layer was dried over sodium sulfate, and the solvents were evaporated under reduced pressure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ROPTs 1 , 2 , 3 , and 4 were synthesized by the acetalization of phthalaldehydic acid (TCI; >98.0%) with methanol (Nacalai Tesque; >99.0%), 2-propanol (Nacalai Tesque; >99.0%), tert -butyl alcohol (Nacalai Tesque; >98.0%), and phenol (Nacalai Tesque; >98.0%), respectively. In­(OTf) 3 (Sigma-Aldrich or Strem; 99%) was used as a catalyst unlike the past examples (Scheme A). After the reaction for a day ( 1 ) or 3 days ( 2 , 3 , and 4 ), the reactions were quenched with Et 3 N (Nacalai Tesque; >98.0%), extracted with dichloromethane, and then washed with water ( 1 , 2 , and 3 ) or aqueous sodium hydroxide solution and then water ( 4 ), followed by brine. The organic layer was dried over sodium sulfate, and the solvents were evaporated under reduced pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above background, we focused on 3-alkoxyphthalides (ROPTs) as a new cyclic hemiacetal ester monomer. As shown in Scheme B, ROPT potentially reacts with a cationic species to generate a carbocation adjacent to both aryl and alkoxy groups (oxocarbenium ion).…”
Section: Introductionmentioning
confidence: 99%
“…In the view point of green chemistry, the use of a catalytic amount of reagents is one of the attractive approaches, in which the ratio between carboxylic acids and alcohols is approximately equal. In 2000, Yamamoto et al reported that 0.1 to 1.0 mol% hafnium (IV) salts in toluene at reflux condition catalyzed the condensation reaction of equimolar amount of carboxylic acids and alcohols ( [67], and L-leucine as an organocatalyst (entry 15) [68] have been reported for the effective catalyst for the esterification using equal or nearly equal amount of carboxylic acids and alcohols. Another approach for the esterification of carboxylic acids with alcohols (2 equiv.)…”
Section: Synthesis Of Carboxylic Acid Esters Using Carboxylic Acids Amentioning
confidence: 99%
“…Esterification of OC to give GC employed the amino acid leucine as a catalyst and geraniol as the solvent (Scheme ). Water is the only stoichiometric byproduct of esterification by this protocol. Because geraniol was used as the solvent for esterification, it was present in a large excess that was easily, quantitatively recovered by filtration.…”
mentioning
confidence: 98%